Rocha Pombo : a solidariedade entre populações como projeto de escrita da história e educação para a formação da nação (1900-1924) - Felipe Augusto Souza Costa (2022)
This research analyzes the following textbooks by Brazilian author Jose Francisco da Rocha Pombo: História das Américas (“History of the Americas” 1st ed. 1900), História do Brasil (curso superior) (“History of Brazil (upper-education level)” 1st ed. 1924), and História do Brasil com muitos mapas históricos e gravuras explicativas (“History of Brazil with many historical maps and explanatory illustrations”, 1st ed. 1918), focusing on the concept of “solidarity” in his construction of a model of history, and on the function of historical education at the beginning of the Republic. These books were written in order to be utilized in schools with the goal of forming the nationality, one of education and textbooks’ functions during this period. The main objective of this study is to analyze and comprehend, in Rocha Pombo’s works, the meaning he gave to the category of “solidarity”, as well as this concept’s political content in the context of his historical writings and of the role of education in his works. It seeks to examine how solidarity emerged as an important point towards the formation of the nationality and of modernist projects in American nations. It also realizes a comparison between the author’s aforementioned textbooks and his texts published in journals, looking to understand his shifts in positioning and perception about history and education. In this way, by means of the history of intellectuals and the history of education it can be verified that Rocha Pombo’s path in order to enter the more well-established circles of early 20th century Brazilian historiography and his place as an intellectual were relevant for the discussion of his ideas.